TRADITIONAL AND MOLECULAR STUDY OF CRYPTOSOPORIDIUM SPP. IN DOMESTIC DOGS IN BAGHDAD CITY,IRAQ - Faraj, A. A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
The aim of this study to investigate the  prevalence of Cryptosoridium spp. in domestic  dogs  in Baghdad city, by  using microscopic  examination(flotation and staining) and molecular techniques .The results revealed that the rate of Cryptosporidium infection was 15% by microscopic examination and 28.6% using PCR, our study showed that the infection rate was 8.5% in males  and 21.42% in  females by microscopic examination , while the infection rate by using PCR in males and females was 21.42%, 35.71% respectively. The percentage of infection in the age  groups 1 year was 20%, 10% respectively by microscopic examination, while by using molecular assay the rate of infection in the age  groups 1 year. This is  the first study in Iraq to detect Cryptosoridium spp. in domestic dogs using molecular technique.